Enhancing the Capacity of Village Disaster Teams Through Community-Based Emergency Management Training - Suharto, Dewi Nurviana; Manggasa, Dafrosia Darmi; Agusrianto, Agusrianto; Rantesigi, Nirva; Langitan, Rosamey Elleke; Hermanto, Raden Bagus Bambang (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2025)
Background: Sintuwulemba Village, Poso Regency, is a high-disaster-risk area where community emergency response capacity is limited. The local Village Disaster Team lacks specific training in managing critical conditions like severe bleeding, respiratory arrest, and shock, often leading to fatal delays. Objectives: This community service initiative aimed to enhance the team's emergency response capabilities through integrated training.Methods: The two-day intensive program utilized lectures, demonstrations, realistic field simulations, and group discussions.Results: Pre- and post-training assessments demonstrated a marked improvement in participant competency, with the average test score increasing from 52% to 88%. The outcomes of this activity include a comprehensive training module, an instructional video, and this report Conclusion: These resources are designed to bolster the long-term resilience and self-sufficiency of the Sintuwulemba community in disaster situations, contributing to the ultimate goal of reducing disaster-related morbidity and mortality.